Social contacts of lonely seniors and seniors living alone as a resource for organization of health and social care - I. N. Moroz; T. G. Svetlovich (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Social contacts of 623 lonely and living alone 60-and- older seniors were studied. A considerable part of respondents indicated the existence of social contacts with relatives (71.9 %) and neighbors, friends, acquaintances (94.2 %). The majority of respondents preferred health and social care though only 69.5 % of respondents could rely on relatives (67.7 % of lonely seniors and 71.4 % living alone seniors).